Benefits and Challenges to Develop Academic Writing Skill Using Open Educational Resource (Oer): Students’ Perspectives - Lia nata safitri; Ahmad Amin Dalimunte (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Open educational resources (OER) can be used by English as a foreign language (EFL) students to improve their language skills, such as writing skills. The purpose of this study was to explore the student’s perceptions on the benefits and challenges faced in using OER to develop their writing skills. To collect the data, researchers involved two main methods used a modified questionnaire and semi-structured interviews with qualitative approach. The study was conducted in one of senior high school in Medan, with eight EFL students as the participants. The data was analyzed in two different ways: content analysis to analyze the questionnaire and thematic analysis of interviews with the participants. The findings revealed that most students had positive perceptions on using OER to develop their writing skills; namely, developing academic writing, better understanding, increased vocabulary, reduce cost, accessible, independent and flexible were the benefits that mentioned by the students. The findings also revealed several challenges that students faced, while using OER to develop their academic writing; namely, lack of feedback, language barrier, and limited internet connection. Our findings suggested in maximizing the use of OER in English language skills, especially improving their understanding of how OER can develop their academic writing skills.